Towards a Conceptual Framework for Defining Iconic Brands: A Critical Review of Studies - Okoeguale, Anthony (Italian Sociological Review, 2022)
Significant academic and managerial interest in brand-consumer relationship has occasioned increasing quantity of literature on the concept. Holt (2004) made a landmark contribution with his conceptualisation of iconic brands, which are arguably aspirational brands. Albeit his works have dominated the discourse on iconic brands, there seem to be more focus on the role of brand owners in defining iconic brands, thus neglecting the place of consumers’ lived experience in the discourse. Recent developments suggest the need for a widening of the conceptual domain to account for the role of consumers’ lived experience in the definition of brands. Consequently, the purpose of this article is to explore the extant literature on the concept of iconic brands in a bid to situate the argument for the inclusion of consumers’ lived experience. The aforementioned exploration addresses the cultural branding model, consumption and the symbolic project of the self, and customer dominant logic. Ultimately, a conceptual model was proposed that highlights the need to investigate the lived experience of consumers. The critical contribution of the article lies in its systematic development of the conceptual domain of iconic brands and the potential this development has for guiding knowledge development including the discussion of an agenda for future research that illustrates its managerial relevance.